Synthesis, physical and chemical research of alkyl-, heterylderivatives of 7’-((4-ethyl-5-thio-4H-1,2,4-triazoles-3-yl)methyl)theophylline - Gotsulya, A. S.; Гоцуля, Андрій Сергійович; Гоцуля, А. С. (Запорізький державний медичний університет, 2016)
Aim. To analyze the alkyl-, heterylderivatives of 7’-((4-ethyl-5-thio-4H-1,2,4-triazoles-3-yl)methyl)theophylline their mother substance has been synthesized and its interaction with halogenalkane and halogenheteryle has been carried out. Methods and results. The physical and chemical properties of the obtained compounds have been studied and their structures have been conﬁrmed by elemental analysis, infrared spectrometry, 1H NMR spectrometry, UV spectrophotometry and gas chromatography mass spectrometry. Preliminary computer study of acute toxicity and biological activity has been also carried out. Results and their discussion. Theophylline was used as starting substance from which through series successive stages of transformation (electrophilic substitution reaction, hydrazinolysis, etheriﬁcation and intramolecular alkaline heterocyclisation) starting thiol and alkyl derivatives were obtained. Alkyl derivatives were obtained in propanol-1 with heating. Synthesized substances were crystallized from methanol. Signals of methyl groups of theophylline, N7-CH2-groups, thioalkyl fragments are ﬁxed in 1H NMR spectrum of obtained compound. Protons of the S-alkyl fragments resonate in a strong ﬁeld as a multiplet in area 1.53–1.01 ppm. Protons of N-C2H5 fragment are ﬁxed also as a multiplet at 1.74–1.62 ppm. CH2-group is presented by protons signals as a singlet at 5.71 ppm. Protons of CH3-group of the xanthine sinton resonate at 2.95 and at 3.25 ppm.Personality of the compounds has been established using chromato-mass spectrometry. Conclusion. 13 New compounds have been obtained and their structure has been conﬁrmed. Indicators of computer evaluation of synthesized compounds using the PASS program have been researched. By means of prediction, results identiﬁed the most perspective compounds for testing the biological activity in vitro. During the analysis of obtained results, it was able to establish that obtained compounds possess different types of biological activity. Diuretic and analeptic activities dominate among the most likely types of that predicted activities for all 13 compounds. Мета роботи – для дослідження алкіл- та гетерилпохідних 7’-((4-етил-5-тіо-4Н-1,2,4-тріазол-3-іл)метил)теофіліну здійснити синтез вихідної речовини й дослідити її взаємодію з галогеналканами та галогенгетерилами. Матеріали та методи. Як вихідну сполуку використали теофілін, з якого через ряд послідовних стадій (реакції електрофільного заміщення, гідразинолізу, етерифікації та внутрішньомолекулярної лужної гетероциклізації) отримали вихідний тіол та його алкілпохідні. Алкілпохідні були синтезовані в середовищі пропанолу-1 при нагріванні. Синтезовані сполуки кристалізовано в середовищі метанолу. Результати. Досліджено фізико-хімічні властивості сполук, що отримали, їхня будова доведена за допомогою елементного аналізу, ІЧ-спектрометрії, 1Н ЯМР-спектрометрії, УФ-спектрофотометрії та хромато-мас-спектрометрії. Сигнали протонів метильної групи теофіліну, метиленової групи, тіоалкільних фрагментів були зафіксовані при здійсненні 1Н ЯМР-спектрометрії. Сигнали протонів S-алкільних фрагментів реєструються у сильному полі у вигляді мультиплета при 1,53–1,01 м. ч. Сигнали протонів N-C2H5 фрагмента також фіксуються у вигляді мультиплета при 1,74–1,62 м. ч. Метиленова група представлена сигналами протонів при 5,71 м. ч. у вигляді синглету. Протони метильної групи резонують у вигляді синтону при 2,95 і при 3,25 м. ч. Індивідуальність сполук, що отримали, встановлена за допомогою хромато-мас-спектрометрії. Здійснили попереднє комп’ютерне дослідження параметрів гострої токсичності та біологічної активності. Висновки. Отримано 13 сполук і доведена їхня структура. Досліджені показники комп’ютерного оцінювання сполук, котрі синтезували, за допомогою онлайн-сервісу PASS. Визначені найбільш перспективні сполуки для тестування in vitro. Під час аналізу результатів вдалося встановити: сполуки, що отримали, можуть володіти різними видами біологічної активності. Серед найбільш імовірних видів активності, котрі передбачені для всіх 13 сполук, домінують сечогінний та аналептичний ефекти. Цель работы – для исследования алкил- и гетерилпроизводных 7’-((4-этил-5-тио-4Н-1,2,4-триазол-3-ил)метил)теофиллина провести синтез исходного вещества и изучить его взаимодействие с галогеналканами и галогенгетерилами. Материалы и методы. В качестве исходного соединения был использован теофиллин, из которого через ряд последовательных стадий (реакции электрофильного замещения, гидразинолиза, этерификации и внутримолекулярной щелочной гетероциклизации) был получен тиол и его алкилпроизводные. Алкилпроизводные были синтезированы в среде пропанола-1 при нагревании. Полученные соединения перекристаллизованы в среде метанола. Результаты. Установлены физико-химические свойства полученных веществ, их строение доказано с помощью элементного анализа, ИК-спектрометрии, 1Н ЯМР-спектрометрии, УФ-спектрофотометрии и хромато-масс-спектрометрии. Сигналы протонов метильной группы теофиллина, метиленовой группы, тиоалкильных фрагментов были зафиксированы при проведении 1Н ЯМР-спектрометрии. Сигналы протонов S-алкильных фрагментов регистрируются в сильном поле в виде мультиплета при 1,53–1,01 м. д. Сигналы протонов N-C2H5 фрагмента также фиксируются в виде мультиплета при 1,74–1,62 м. д. Метиленовая группа представлена сигналами протонов при 5,71 м. д. в виде синглета. Протоны метильной группы резонируют в виде синтона при 2,95 и при 3,25 м. д. Индивидуальность полученных соединений установлена с помощью хромато-масс-спектрометрии. Осуществлено предварительное компьютерное исследование параметров острой токсичности и биологической активности. Выводы. Получено 13 соединений и доказана их структура. Исследованы показатели компьютерной оценки синтезированных соединений с помощью онлайн-сервиса PASS. Определены наиболее перспективные соединения для тестирования in vitro. В ходе анализа результатов удалось установить, что полученные соединения могут обладать различными видами биологической активности. Среди наиболее вероятных видов активности, которые могут проявиться у всех 13 соединений, доминируют мочегонный и аналептический эффекты.
Синтез і фізико-хімічні дослідження алкіл- та гетерилпохідних 7’-((4-етил-5-тіо-4Н-1,2,4-тріазол-3-іл)метил)теофіліну
Синтез и физико-химические исследования алкил- и гетерилпроизводных 7’-((4-этил-5-тио-4Н-1,2,4-триазол-3-ил)метил)теофиллина
Keywords: 1,2,4-triazoles; Theophylline; Synthesis; IR-spectrometry; 1H NMR spectrometry; 1,2,4-триазол; теофілін; синтез; ІЧ-спектрометрія; 1Н ЯМР спектрометрія; теофиллин; ИК-спектрометрия; 1Н ЯМР-спектрометрия